2003
DOI: 10.1159/000070295
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Sertoli-Leydig Cell Tumor, Endometrioid-Like Yolk Sac Tumor, and Y-Chromosomal Material

Abstract: Sertoli-Leydig cell tumors (SLCTs) are rare neoplasms, accounting for less than 0.2% of ovarian tumors. The endometrioid-like variant of yolk sac tumor (YST) is very rare, and the most extensive series reported only 8 cases. We present a case of ovarian SLCT with endometrioid-like YST in a patient with a 46,XX karyotype with Y-chromosomal material. A 26-year-old woman had undergone a right salpingo-oophorectomy for SLCT with endometrioid-like YST. Chromosomal analysis revealed a 46,XX karyotype with Y-chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…There is a possible association of SLCT with sex chromosome abnormalities; it was report one case of SLCT with X chromosome mosaicism (45X/46XX/47XXX) [12] and one case of female karyotype with Y-chromosomal material insertion into chromosome 1 in an ovarian SertoliLeydig cell tumor with endometrioid-like yolk sac tumor [13]. In our case the chromosomal analysis revealed a 46,XX karyotype.…”
Section: Discussionsupporting
confidence: 46%
“…There is a possible association of SLCT with sex chromosome abnormalities; it was report one case of SLCT with X chromosome mosaicism (45X/46XX/47XXX) [12] and one case of female karyotype with Y-chromosomal material insertion into chromosome 1 in an ovarian SertoliLeydig cell tumor with endometrioid-like yolk sac tumor [13]. In our case the chromosomal analysis revealed a 46,XX karyotype.…”
Section: Discussionsupporting
confidence: 46%
“…The FISH analysis confirmed this, showing three to four signals for 22q11.2 in 30% of the analysed nuclei (Table 2). De Giorgi et al [1] presented a case of ovarian SLCT with endometrioid-like yolk sac tumour in a 26-year-old patient with a 46,XX karyotype with Y-chromosomal material insertion into chromosome 1. A well-differentiated SLCT of the ovary in a 48-old-year Japanese woman with symptoms of virilisation and a 45,X/46XX/47XXX karyotype is reported by Hitosugi et al [3].…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, some few cytogenetic studies of SLCT of the ovary, which revealed genetic aberrations affecting the sex chromosome [1,3,4]. Trisomy 8 was detected in a metastasizing ovarian SLCT as sole karyotypic aberration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies of ovarian SLCTs revealed karyotypic abnormalities affecting the sex chromosomes, including a case with X-chromosome mosaicism [35] and another case of a 46,XX karyotype with insertion of Ychromosomal material into chromosome 1 [36]. Another cytogenic study of a metastasizing SLCT identified trisomy 8 as the only karyotypic abnormality [37].…”
Section: Abstract: Dicer1 Foxl2 Cyp19a1 Aromatasementioning
confidence: 99%